From wood pellets to wood chips, risks of degradation and emissions from the storage of woody biomass – A short review. (February 2016) - Alakoski, Esa; Jämsén, Miia; Agar, David; Tampio, Elina; Wihersaari, Margareta
Abstract: The compounds in stored woody biomass degrade as a result of chemical and/or biological processes during storage. These processes produce gaseous emissions. Recent studies concerning gaseous emissions from wood pellet storages are reviewed herein. The applicability of the results from pellet research to wood chips is discussed. Thorough scientific understanding on the storage phenomena of wood chips is extremely important as the threat of climate change and the need to reduce greenhouse gas emissions have led to an increased need to large scale wood chip storage to ensure supply. Typically the gases produced from stored woody biomasses are carbon monoxide (CO), carbon dioxide (CO2 ), methane (CH4 ), and other volatile hydrocarbons e.g. aldehydes and terpenes. CO2 and CH4 are greenhouse gases with high global warming potential. Chemical degradation via auto-oxidation of fats and fatty-acids seems to be the dominant mechanism for off-gassing from stored wood pellets, whereas biological processes are mainly responsible for the gaseous emission from wood chips. In confined storage spaces gaseous emissions may lead to oxygen depletion. Oxygen depletion together with a high CO concentration poses a serious health risk for those working in such conditions. The degradation processes also result in dry matter losses and in spontaneous heating and in the worst case, especially in large piles, spontaneous ignition of the stored material. Thorough and systematic scientific studies on degradation processes and their effects are needed in order to understand and minimise risks from large scale wood chips storage to human health, environment and property.